Effects of GLP-1 and GIP on cholinergic-induced contractility in isolated jejunal muscle from obese patients with and without type 2 diabetes mellitus - Malinauskas, Mantas; Stukas, Darius; Rysevaite-Kyguoliene, Kristina; Gudaityte, Rita; Kupčinskas, Limas; Casselbrant, Anna; Jankauskaite, Lina; Maleckas, Almantas (Frontiers in Physiology, 2026)
BackgroundIntestinal dysmotility in type 2 diabetes mellitus (T2DM) may involve impaired cholinergic and incretin-mediated regulation. This study compared cholinergic-induced jejunal contractility and evaluated the effects of Glucagon like peptide-1 (GLP-1) and Gastric inhibitory polypeptide (GIP) in relation to the expression of these peptides, their receptors, and Dipeptidyl peptidase 4 (DPP-4) in jejunal muscle of obese patients with and without T2DM.MethodsJejunal samples were collected from 32 obese patients undergoing bariatric surgery (14 with and 18 without T2DM). Jejunal muscular tissue was examined for expression of GLP-1, GIP, and for expression and localization of DPP-4 and incretin receptors (GLP-1R and GIPR). In addition, DPP-4 enzymatic activity was quantitatively assessed. Contractility of circular and longitudinal muscle strips was assessed in vitro following bethanechol stimulation, with or without GLP-1 or GIP.ResultsGLP-1 receptors were detected in smooth muscle nuclei and enteric ganglia, while GIP receptors localized to both muscle layers. DPP-4 was present in neural and muscular compartments. In T2DM, GIPR and DPP-4 expression and activity were increased, while GIP protein was reduced. GLP-1 protein levels tended to be higher. Longitudinal muscle contractility independent of neural input was reduced in T2DM. GLP-1 selectively inhibited circular muscle contractions in both groups, whereas GIP had no effect.ConclusionThis study demonstrates that reduced cholinergic activity in longitudinal muscle, lower GIP, and increased GLP-1 in T2DM indicate a shifted local incretin environment that may collectively suppress jejunal contractility.